2014
DOI: 10.15252/emmm.201403927
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell‐specific inhibition of MYC function using small molecule inhibitors of the HUWE1 ubiquitin ligase

Abstract: Deregulated expression of MYC is a driver of colorectal carcinogenesis, necessitating novel strategies to inhibit MYC function. The ubiquitin ligase HUWE1 (HECTH9, ARF-BP1, MULE) associates with both MYC and the MYC-associated protein MIZ1. We show here that HUWE1 is required for growth of colorectal cancer cells in culture and in orthotopic xenograft models. Using high-throughput screening, we identify small molecule inhibitors of HUWE1, which inhibit MYC-dependent transactivation in colorectal cancer cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 52 publications
2
106
0
1
Order By: Relevance
“…We do acknowledge, however, that there are conflicting data published (14,24), and further acknowledge the possibility that Mule may function differently if it is overexpressed. Thus, we are attempting to understand whether the role of Mule in an established adenoma or tumor would differ from its role in adenoma initiation, and whether Mule overexpression in colon cancer results because of its signaling feedback that may occur if mutations render it inactive, as is classically the case for p53 in cancer (25).…”
Section: Discussionmentioning
confidence: 89%
“…We do acknowledge, however, that there are conflicting data published (14,24), and further acknowledge the possibility that Mule may function differently if it is overexpressed. Thus, we are attempting to understand whether the role of Mule in an established adenoma or tumor would differ from its role in adenoma initiation, and whether Mule overexpression in colon cancer results because of its signaling feedback that may occur if mutations render it inactive, as is classically the case for p53 in cancer (25).…”
Section: Discussionmentioning
confidence: 89%
“…1). Mechanistically, evidence was provided that HUWE1 inhibitors shift the activating MYC/MAX complex to a repressive MIZ1/MYC/MAX complex to deactivate a MYC-dependent oncogenic network (69), offering a further strategy to target MYC-addicted PDACs.…”
Section: Targeting Myc Indirectlymentioning
confidence: 99%
“…On the one hand, numerous studies carried out in different cancer cell lines have shown that the transcriptional repression of Miz-1 by c-Myc is relevant in many different stages of the carcinogenesis process (13). Interestingly, on the other hand, another recent study showed that high levels of Miz-1 cause the repression of c-Myc transcriptional transactivation (14). These results have led to the interesting hypothesis that the c-Myc/Miz-1 balance can dictate cell fate by controlling the transcription of gene networks (15).…”
Section: Ink4mentioning
confidence: 99%
“…In fact, in cancer cells, Miz-1 is found to co-localize with c-Myc at many transcription start sites where INR sequences are present. Most interestingly, Miz-1 can inhibit c-Myc transactivation of genes involved in tumorigenic programs (14,22). Despite such a critical role in the normal and oncogenic biology of the cell, it is not known whether all of the ZFs or only subsets bind and recognize the Miz-1 consensus sequence, the INR element, or other nonspecific DNA sequences.…”
Section: Ink4mentioning
confidence: 99%